PENGARUH PEMAHAMAN MATERI HAK ASASI MANUSIA TERHADAP KEBEBASAN BERPENDAPAT SISWA KELAS XII DI SMK MUHAMMADIYAH 2 PEKANBARU - Rozi Agus Trisanti; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by an understanding of human rights material on freedom of opinion of class XII students at SMK Muhammadiyah 2 Pekanbaru. This is seen from the understanding of students in exercising the right to freedom of opinion. The formulation of the problem in this research is “Is there any influence of understanding human rights material “cases of human rights violations “on freedom of opinion of class XII students at SMK Muhammadiyah 2 Pekanbaru?”This study aims to determine the effect of understanding human rights material “cases of human rights violations “on freedom of opinion of class XII students at SMK Muhammadiyah 2 Pekanbaru. This research was conducted at SMK Muhammadiyah 2 Pekanbaru conducted in July to August 2019. This research uses a quantitative descriptive approach. Data collection techniques using observation, questionnaire, interview, and documentation. Then in this study it is evident that the understanding of human rights material “cases of human rights violations”in class XII students at SMK Muhammadiyah 2 Pekanbaru is included in the low category.Key Words: Human Rights Material, Freedom Of Opinion